PERAN GURU DALAM MEMBENTUK KARAKTER DISIPLIN SISWA MELALUI MENTORING PADA MATA PELAJARAN AL-QURAN HADITS DI MADRASAH ALIYAH (MA) AL-KAHFI SURAKARTA KELAS 11 TAHUN AJARAN 2024/2025 - 'Isa Tsaqila Ulul Azmi; Muin Abdullah; Yuni Safitri (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
The objectives of this study are: (1) To determine the role of teachers in implementing the mentoring program in the Al-Qur’an Hadith subject at Al-Kahfi Islamic Senior High School (MA) Surakarta, and (2) To determine the role of teachers in shaping students’ discipline character through the mentoring program. This research employs a qualitative correlational approach with research subjects consisting of teachers (mentors) and 30 students of grade 11 at MA Al-Kahfi Surakarta. Data were collected through observation, interviews, and documentation, while data analysis was conducted using source triangulation to test data validity. The results of the study show that: (1) The teachers’ roles in implementing the mentoring program include being role models, advisors, mentors, and evaluators, with mentoring activities conducted through the halaqah method; (2) The teachers’ roles in shaping students’ discipline character are reflected in their efforts to set examples of discipline, guide undisciplined students, give corrective feedback for violations, and evaluate students’ level of discipline. Thus, the teachers’ roles in the mentoring program have proven to contribute positively to the formation of students’ discipline character, particularly through exemplary behavior and intensive guidance within the Al-Qur’an Hadith learning process.